2015
DOI: 10.1007/s40204-015-0043-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature, pH and simulated biological solutions on swelling and structural properties of biomineralized (CaCO3) PVP–CMC hydrogel

Abstract: Biomaterials having stimuli response are interesting in the biomedical field. This paper reports about swelling response and internalstructural of biomineralized (CaCO3) polyvinylpyrrolidone (PVP) carboxymethylcellulose (CMC) hydrogel having various thicknesses (0.1–0.4 mm). Samples were tested in aqueous solution using temperature ranges from 10 to 40 °C; pH varies from 4 to 9, time 60 min. In addition, an experiment was conducted in the presence of simulated biological solutions (SBS): glucose (GS), physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Figure represents the swelling trend of the St‐Ch 50 hydrogel in the solutions of distilled water, glucose, and urea. It can be revealed that the binding of glucose moieties with the hydrogel gradually leads to an increase of the charge density within the hydrogel, hence increases the hydrophilicity within the hydrogel, which finally leads to the rise in the swelling capacity . Similar to the glucose solution, the same trend of swelling behavior is observed in the urea solution.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Figure represents the swelling trend of the St‐Ch 50 hydrogel in the solutions of distilled water, glucose, and urea. It can be revealed that the binding of glucose moieties with the hydrogel gradually leads to an increase of the charge density within the hydrogel, hence increases the hydrophilicity within the hydrogel, which finally leads to the rise in the swelling capacity . Similar to the glucose solution, the same trend of swelling behavior is observed in the urea solution.…”
Section: Resultsmentioning
confidence: 67%
“…This could be because of the presence of hydroxyl groups of starch, amino groups of chitosan, and carboxyl groups of CA. In pH = 7.5, water molecules undergo H 2 bonding so more space is generated for the molecules to penetrate inside, thus the material swells more . Figure represents the swelling trend of the St‐Ch 50 hydrogel in the solutions of distilled water, glucose, and urea.…”
Section: Resultsmentioning
confidence: 99%
“…Gómez-Carracedo et al The first endotherm with a heat of fusion 89.74 J/g, can be attributed to the evaporation of unbound water in the crosslinked polymer and second endotherm (108.6 J/g) can be due to anhydride formation in the polymer. [52]…”
Section: Characterizationmentioning
confidence: 99%
“…Some researchers studied the hydrothermal effect on the static and dynamic mechanical properties of CMC/PVP hydrogel films for using them as a food packaging material . Whereas, other researchers synthesized CaCO 3 ‐based bio‐mineralized CMC/PVP hydrogels and studied their swelling, structural and visco‐elastic behavior . In addition, CMC/PVP hydrogels synthesized by γ‐rays irradiation for the potential application in agriculture and wound dressing were also reported.…”
Section: Introductionmentioning
confidence: 99%